The Bill Elimination on Sexual Violence: Importance for Indonesian Women - Herawati, Ratna; Purwanti, Ani; Pinilih, Sekar Anggun Gading (International Journal of Criminology and Sociology, 2021)
This paper aims to find out to understand the importance of the bill in improving the quality of life of Indonesian women, as well as the vision, mission, and direction of President Joko Widodo in 2019-2024. This research was conducted by using the juridical empirical method, by looking at problems in the community, then looks for the legal basis and expert opinion, and is processed using the triangulation method. The results showed that increasing cases regarding various types of violence against women in various places cause the government needs to make a regulation needed to eliminate sexual violence through the bill. Hence, the Bill on the Elimination of Sexual Violence is urgently needed in Indonesia. The findings also noted that previous regulations have not sufficiently regulated the form of protection for women against sexual violence. The main conclusion of the study is that the bill is a form of the government's responsibility to ensure the fulfillment of these rights: the right to handle, right to protection, and right to recovery.